2017
DOI: 10.4155/fmc-2016-0203
|View full text |Cite
|
Sign up to set email alerts
|

Practical Applications of Matched Series Analysis: Sar Transfer, Binding Mode Suggestion and Data Point Validation

Abstract: The presence of SAR transfer can confirm the perceived binding mode overlay of different chemotypes or suggest new arrangements between scaffolds that may have gone unnoticed. The absence of series correlation can highlight the presence of inconsistent data points where assay values should be reconfirmed, or provide challenge to any project dogma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The complete leave-one-out MMS analysis of Pfizer’s database showed that more than one-third of the 1 million random predictions achieved a strong correlation with potency ( R 2 > 0.49), further indicating that this method can greatly facilitate MMS for scaffold replacement and optimization. Based on the combination of MMS network and structural graph, Hunt et al observed that MMS analysis provides more detailed information on compound alignments or their binding modes to be explored, providing possible hypotheses for further lead optimization …”
Section: Practical Applications Of Mmpamentioning
confidence: 99%
See 1 more Smart Citation
“…The complete leave-one-out MMS analysis of Pfizer’s database showed that more than one-third of the 1 million random predictions achieved a strong correlation with potency ( R 2 > 0.49), further indicating that this method can greatly facilitate MMS for scaffold replacement and optimization. Based on the combination of MMS network and structural graph, Hunt et al observed that MMS analysis provides more detailed information on compound alignments or their binding modes to be explored, providing possible hypotheses for further lead optimization …”
Section: Practical Applications Of Mmpamentioning
confidence: 99%
“…Based on the combination of MMS network and structural graph, Hunt et al observed that MMS analysis provides more detailed information on compound alignments or their binding modes to be explored, providing possible hypotheses for further lead optimization. 124 MMPA Public Tools: Web Servers, Software, and Databases. To better curate and exchange knowledge on drug hunting, several MMPA tools have been developed to facilitate the analysis of the relationship between chemical structures and biological effects or physiochemical properties, thus accelerating the design of new drugs.…”
Section: ■ Practical Applications Of Mmpamentioning
confidence: 99%
“…Matched molecular series analysis (MMSA) has emerged as a new computational data analysis approach to support the compound optimization process. Specifically, it attempts to answer the question, “what other R-groups are worth evaluating in analogue series?” Wawer and Bajorath first introduced the concept of matched molecular series (MMS) as an extension of matched molecular pair analysis (MMPA, Figure a) to capture structure–activity relationship (SAR) information from large compound databases. Since then, MMSA has been studied extensively in the context of SAR transfer as an idea generation ,, and semiquantitative activity prediction tool , but not yet for ADMET property prediction.…”
Section: Introductionmentioning
confidence: 99%
“…With the aid of structural data and models such as those listed below, the reason for discontinuities can be investigated and evaluated. Finding and explaining activity cliffs with the inclusion of structural data into quantitative structure–activity relationship (QSAR) models, SAR transfer between molecular series, and visualization of activity patterns as well as high‐impact sites are some of the main applications of the 3D MMP concept. Depending on how 3D similarity is defined, scaffold hopping can be realized as well …”
Section: Introductionmentioning
confidence: 99%